2010
DOI: 10.1111/j.1365-3121.2009.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pyroclastic soil on epikarst formation: a test study in southern Italy

Abstract: Epikarst formation in the southern Apennines (Italy) was hypothesized to be significantly influenced by diffuse rainwater infiltration through soil of pyroclastic origin. Multidisciplinary investigations were carried out at an experimental field site to test this hypothesis. At this site, other factors influencing epikarst formation can be assumed invariant. A direct relationship was observed between soil thickness and epikarst thickness. This relationship supports the hypothesis that the pyroclastic soil play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Where the carbonate aquifers are juxtaposed with medium permeable Plio-Quaternary epiclastic and alluvial deposits, a groundwater exchange can exist. A subordinate perched groundwater flow also occurs in the surficial part of karst aquifers, where the different deepening of the epikarst (Celico et al, 2010), as well as stratigraphic and tectonic factors, can generate seasonal and ephemeral springs. The groundwater yield of the Campania's karst aquifers varies from 0.015 to 0.038 m 3 s −1 km −2 (Allocca et al, 2007(Allocca et al, , 2009.…”
Section: Climate and Hydrogeological Characteristics Of The Campania mentioning
confidence: 99%
“…Where the carbonate aquifers are juxtaposed with medium permeable Plio-Quaternary epiclastic and alluvial deposits, a groundwater exchange can exist. A subordinate perched groundwater flow also occurs in the surficial part of karst aquifers, where the different deepening of the epikarst (Celico et al, 2010), as well as stratigraphic and tectonic factors, can generate seasonal and ephemeral springs. The groundwater yield of the Campania's karst aquifers varies from 0.015 to 0.038 m 3 s −1 km −2 (Allocca et al, 2007(Allocca et al, , 2009.…”
Section: Climate and Hydrogeological Characteristics Of The Campania mentioning
confidence: 99%
“…Moreover, given their proximity to volcanic centers ( Fig. 1), these aquifers were singularly covered by variable thicknesses of ash-fall pyroclastic deposits (De Vita et al, 2006 that erupted during the Quaternary, whose presence influences the epikarst development (Celico et al, 2010). Regional hydrogeological studies carried out in the southern Apennines analysed groundwater circulation in main karst aquifers by understanding geological and structural constraints that control groundwater paths and assessing large groundwater bodies outflowing chiefly in basal springs, with mean annual discharges varying from 0.1 to 5.5 m 3 s −1 .…”
Section: Hydrogeology Of Karst Aquifers and Climatic Characteristics mentioning
confidence: 99%
“…White (2004) considered that while the A and O soil horizons (the American soils classification system) should be excluded from the epikarst, normally the B horizon that fills the solutional voids, should be included. Celico et al (2010) concluded that epikarst formation can be reliant on soil thickness. Williams (2004) conceded that where soil is present, it would most likely moderate infiltration and provide further storage of water.…”
Section: Introductionmentioning
confidence: 99%